2016
DOI: 10.1186/s13256-016-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Median sacral artery injury following a bone marrow biopsy successfully treated with selective trans-arterial embolization: a case report

Abstract: BackgroundIatrogenic arterial injury during bone marrow biopsy is an extremely rare complication. We present unreported complication of median sacral artery injury that was managed successfully with endovascular treatment.Case presentationA 22-year-old Caucasian man known to have end-stage renal disease secondary to Senior-Loken syndrome presented with anemia. He underwent an investigation with bone marrow biopsy that was complicated by hypotension and a further significant drop in his hemoglobin level. Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…While bone marrow biopsy complications may not be directly associated with obesity, the inciting factor is often an inability to determine landmarks and/or needle position. [21][22][23][24][25][26] Performing bone marrow biopsy under CT guidance eliminates the need for bony landmarks and should be considered as a safe alternative in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While bone marrow biopsy complications may not be directly associated with obesity, the inciting factor is often an inability to determine landmarks and/or needle position. [21][22][23][24][25][26] Performing bone marrow biopsy under CT guidance eliminates the need for bony landmarks and should be considered as a safe alternative in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Al Zahrani et al reported the first case of median sacral artery involvement. An emergency angiography and embolization procedure was performed using seven micro-coils ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic injury during bone marrow biopsy is rare, but has been reported in the literature (95). Reported cases of arterial injury include circumflex iliac artery, iliolumbar artery, superior gluteal artery, median sacral artery, and anterior hypogastric artery (86,(96)(97)(98)(99)(100)(101).…”
Section: Bone Marrow Biopsymentioning
confidence: 99%